Functional antagonism between ΔNp63α and GCM1 regulates human trophoblast stemness and differentiation - Wang, Liang-Jie; Chen, Chie-Pein; Lee, Yun-Shien; Ng, Pui-Sze; Chang, Geen-Dong; Pao, Yu-Hsuan; Lo, Hsiao-Fan; Peng, Chao-Hsiang; Cheong, Mei-Leng; Chen, Hungwen (Nature communications, 2022)
The combination of EGF, CHIR99021, A83-01, SB431542, VPA, and Y27632 (EGF/CASVY) facilitates the derivation of trophoblast stem (TS) cells from human blastocysts and first-trimester, but not term, cytotrophoblasts. The mechanism underlying this chemical induction of TS cells remains elusive. Here we demonstrate that the induction efficiency of cytotrophoblast is determined by functional antagonism of the placental transcription factor GCM1 and the stemness regulator ΔNp63α. ΔNp63α reduces GCM1 transcriptional activity, whereas GCM1 inhibits ΔNp63α oligomerization and autoregulation. EGF/CASVY cocktail activates ΔNp63α, thereby partially inhibiting GCM1 activity and reverting term cytotrophoblasts into stem cells. By applying hypoxia condition, we can further reduce GCM1 activity and successfully induce term cytotrophoblasts into TS cells. Consequently, we identify mitochondrial creatine kinase 1 ( CKMT1 ) as a key GCM1 target crucial for syncytiotrophoblast differentiation and reveal decreased CKMT1 expression in preeclampsia. Our study delineates the molecular underpinnings of trophoblast stemness and differentiation and an efficient method to establish TS cells from term placentas. Trophoblast stem cells can be derived from human blastocysts and first-trimester, but not term, cytotrophoblasts. Here the authors show that induction efficiency of cytotrophoblast is determined by antagonism between GCM1 and ΔNp63α and manipulating this antagonism facilitates derivation of TS cells from term placenta.